Optimum Design of Cross-Flow In-Line Tube Banks at Constant Wall Temperature. Issue 6 (12th April 2016) - Yilmaz, Alper; Yilmaz, Tuncay
Abstract : For many applications, it is important to transfer a given amount of heat with minimum possible volume of heat exchanger for a given pressure loss and efficiency. In this study, such optimum design of cross-flow in-line tube banks at constant wall temperature is carried out. For this purpose, two different methods, namely, the Gnielinski + Gaddis and Zukauskas methods, for the calculation of heat transfer coefficient and pressure loss in tube banks are used. By prescribing the tube diameter, heat exchanger efficiency, and pressure loss of heat exchanger, the pitch length and tube numbers in the flow direction are determined for the condition of the maximum heat flow per heat exchanger volume. For a given value of total heat to be transferred, the length, the height, and the width of heat exchanger can be determined. Equations for this optimum design are derived using appropriate dimensionless numbers. The methodology of the optimum design is explained for a practical example.